Paul the Trojan Horse: The Legacy of Triumph in Philippians - Flexsenhar, Michael, III (Journal for the study of the New Testament, 2021)
This article describes the use of Philippians in triumphalist narratives about the rise of Christianity. Outlining the place of two key terms in the reception history of the letter – praetorium (Phil. 1.13) and ‘Caesar’s household’ (Phil. 4.22) – the article critiques the underlying assumptions and ideologies that have often guided its interpretation, focusing especially on the use of canonical Acts. A brief survey of the evidence for these two key terms in their original context – literary, epigraphic, lexicographical – suggests new interpretive possibilities for understanding Paul’s life and letter.